Aerosol effects on the timing of warm rain processes. Issue 11 (2nd June 2015) - Dagan, Guy; Koren, Ilan; Altaratz, Orit
Abstract Warm rain production as the end result of all clouds' processes is highly affected by aerosol loading and properties. Here an axisymmetric bin microphysics cloud model is used to study the aerosol's effects on the competition and synergy between processes in a single convective cloud, to provide a baseline for studies of aerosol effects on cloud fields. A new measure that considers the timing of processes is suggested for evaluating the optimal conditions for maximum rain yield. These conditions are linked to an optimal aerosol concentration (Nrain_op), which drives similar time intervals to maximum collected mass and to maximum vertical development. Nrain_op is a function of cloud size and thermodynamic conditions. Giant cloud condensation nuclei (GCCN) impact was shown before to precede the initiation of collision‐coalescence and to increase the amount of rain from polluted clouds. Here we show that the GCCN effect is important only under aerosol conditions above Nrain_op.